2021
DOI: 10.1149/1945-7111/abde7d
|View full text |Cite
|
Sign up to set email alerts
|

Deconvoluting Reversible and Irreversible Degradation Phenomena in OER Catalyst Coated Membranes Using a Modified RDE Technique

Abstract: The suitability of the Thin-Film RDE (TF-RDE) technique to rigorously evaluate stability measurements for the oxygen evolution reaction (OER) was recently questioned. The main issue was the inability to deconvolute bubble blockage of catalytic active sites from catalyst dissolution using the TF-RDE technique. It is also possible that the low-loading of TF-RDE OER catalysts exacerbates the effect of bubble blockage. In this work, the modified rotating disk electrode (MRDE) is used with commercial catalyst coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Chronopotentiometry tests were carried out at fixed current densities of 10 or 100 mA cm –2 . Accelerated degradation testing (ADT) was measured between 0–1.4 V vs. Ag/AgCl using 100 mV s −1 scan rate 63 . For the electrochemical double-layer capacitance (EDLC) measurements, open circuit potentials (OCPs) vs. the Ag/AgCl were firstly recorded for 30 min to reach rather stable values.…”
Section: Methodsmentioning
confidence: 99%
“…Chronopotentiometry tests were carried out at fixed current densities of 10 or 100 mA cm –2 . Accelerated degradation testing (ADT) was measured between 0–1.4 V vs. Ag/AgCl using 100 mV s −1 scan rate 63 . For the electrochemical double-layer capacitance (EDLC) measurements, open circuit potentials (OCPs) vs. the Ag/AgCl were firstly recorded for 30 min to reach rather stable values.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the gap between the two systems is smaller than that previously reported by our group . Several hypotheses endeavoring to explain the discrepancy between AMS and MEA have been reported in the literature, from the formation of oxygen microbubbles within the CL shielding the active sites to the local pH and experimental timeframes . Future research efforts are needed in order to unravel to what extent the mentioned effects contribute to the observed discrepancy.…”
Section: Correlation Between Electrochemical Cell Performance and Cat...mentioning
confidence: 59%
“…Addressing O 2 bubble formation, previous literature studies investigating the blockage of active sites by O 2 bubbles have employed 30 min Ar purges of their cell and electrolyte after a designated time of electrochemical testing, and have been able to partially recover electrochemical OER performance after purging. 54,56 Additionally, Hartig-Weiss and co-workers have recently shown that ultrasonication of their electrolyte, which rapidly removes O 2 bubbles from electrode surfaces, enables constant OER current from their Ir disk working electrode over 450 s. 53 However, when we conducted 30 min Ar purging throughout stability testing of our glassy carbon-based IrO x electrodes, we did not observe any significant OER performance improvement after Ar purging, and there was no significant deviation in OER performance over the course of the test compared to stability testing without purging (Figure S11). The discrepancy in performance recovery results reported herein and that of the previously mentioned studies likely derives from the difference in experiments: previous reports conducted electrochemical testing that was either relatively short in duration compared to the stability tests conducted in this work or involved a significantly modified working electrode that did not have a glassy carbon component.…”
Section: Resultsmentioning
confidence: 99%
“…Additional possible sources of electrode instability are disconnection of the catalyst from the substrate surface as well as the formation of O 2 bubbles at the catalyst surface, which can block catalyst active sites. Concerning the possibility of physical disconnection of the catalyst, we cannot rule this out as a possible contributing factor toward the increase in charge transfer resistance observed throughout stability testing, as discussed later in section 3.3. Addressing O 2 bubble formation, previous literature studies investigating the blockage of active sites by O 2 bubbles have employed 30 min Ar purges of their cell and electrolyte after a designated time of electrochemical testing, and have been able to partially recover electrochemical OER performance after purging. , …”
Section: Results and Discussionmentioning
confidence: 99%